(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of arthroscopic single-bundle Anterior Cruciate Ligament Reconstruction (ACLR ) using Hamstring auto graft in patients with complete Anterior Cruciate Ligament (ACL) rupture. Methods: This descriptive study was conducted in Liaquat National Hospital, Karachi from 20th March 2016 to 20th March 2021.All adults patients with ACL tear fulfilling the inclusion criteria were treated arthroscopically with single bundle ACLR using Hamstring auto graft. Functional outcome at two years were assessed with International Knee Documentation Committee (IKDC) scoring system and compared with pre operative value. P value was calculated with Chi-square test and Independent Sample-t test. P value <0.05 was considered significant Results: We performed 136 single bundle arthroscopic ACLR using Hamstring auto graft. The mean age of our patients were 33.28±10.22 years. Male patients were 128(94.11%) and female patients were 8(5.88%). Right sided ACLR was performed in 88(64.70%) patients and left sided in 48(35.29%) patients. The mean pre-operative IKDC score was 43.45 ±10.68 and improved to 89.87±13.40 at two years follow up.(p<0.05). Conclusion: Excellent functional outcome was achieved with arthroscopic single bundle Hamstring ACLR in majority of our patients. We recommend Single bundle arthroscopic Hamstring ACLR as technique of first choice in patients with ACL rupture.